Experiences of Abused Health Care Workers – Findings from an online qualitative self-report study on child psychiatry (Academic Journal of Internal Affairs, 2023)
Aim: Emergency psychiatric care for children is a priority. It is inevitable that sometimes in some situations patients or their relatives abuse psychiatric staff. There are many factors that facilitate this violence, but also some that are protective. It is a crucial question whether the causes of abuse can be found in the patients, in external factors or in the situation.Methodology: Following an extensive Hungarian and international literature review, Authors used a self-developed semi-structured online questionnaire with a total of ten questions, involving 51 participants, from which 21 responded. The topics of the questions were: definition of intentional and non-intentional violence, description of the abuse, perceived risk factors, consequences of the incident, cause and goal, treatment, reporting, prevention, and other comments. The data corpus was examined using content analysis and coded in two stages.Findings: During the coding process, Authors found that situational causes underlie abuse in most areas. In case descriptions, external causes were also emphasized. In topics consequences and goals, patient-related criteria were the most frequent, and external factors were the first only in topic of risk factors. Staff-patient interaction is a crucial issue related to violence against health workers, but the potentially triggering psychiatric disorder of the child cannot always be excluded.Value: Most psychiatric disorders are caused by early trauma, and trauma is underpinned by adverse childhood experiences and deviant parental behaviour. However, the hospital is a part of a larger system and health problems have social roots. It should be underlined that direct causes of abuse are hidden in the staff-patient interaction, but in many cases parental deviance is also responsible for the onset of psychiatric disorders. Our research may contribute to a deeper understanding of this phenomenon and provide a basis for future quantitative research.
Keywords: trauma; adverse childhood experiences; emergency child psychiatry; workplace violence